Pengaruh Kualitas Produk, Harga Dan Promosi Terhadap Keputusan Pembelian (Studi Pada Batik Silabi Kota Metro) - Nur Aulia Rahmahdani; Selamet Fuadi; Suwarto (Jurnal Manajemen DIVERSIFIKASI, 2025)
This study aimed at knowing whether product quality was a purchasing decision on batik Silabi Metro city. To find out whether the price of the purchase decision on batik Silabi Metro city. To find out whether promotion on purchasing decisions at Silabi batik Metro city. To find out whether product quality, price and promotion have a significant effect on purchasing decisions at Silabi batik Metro city. The sample in this study amounted to 96 consumers at batik Silabi metro city. Data collection using a questionnaire and data analysis using Validity Test, Reliability Test, Normality Test, Linearity Test, Multicollinearity Test, Multiple Linear Analysis Test, t test, f test, determination r test and Statistical Hypothesis Test. Using the SPSS data processing program. The results showed that 1. product quality had a positive and significant effect on purchasing decisions. 2. Price had a negative and insignificant effect on Purchasing Decisions. 3. Promotion had a positive and significant effect on Purchasing Decisions. 4. Product Quality, Price, and Promotion had a positive and significant effect on Purchasing Decisions.